The Influence of Leadership Style of the Head of the Ward, Work Culture, and Work-load on the Performance of Implementing Nurses in the Inpatient Ward of Budiasih Hospital, Serang - Andi Riska Wahyu Nengsih; Dudung Hadiwijaya; Priyo Susilo (Eduvest - Journal of Universal Studies, 2024)
This study aims to determine the influence of leadership style variables (X1), work culture (X2), and workload (X3) on performance variables (Y) on executive nurses in the Inpatient Room of Budiasih Serang Hospital both partially and simultaneously. The method used in this research is quantitative method, with respondents, namely all executive nurses in the inpatient room totaling 87 people. The analysis technique used is multiple linear regression analysis, correlation test, coefficient of determination test, with hypothesis testing methods, namely t test and F test. The results of hypothesis testing state that partially and simultaneously the variables of leadership style (X1), work culture (X2), and workload (X3) have a positive and significant effect on the performance variables of executive nurses, with a partial effect of 51%, 76%, and 12.6%, respectively. However, the magnitude of the simultaneous influence of the three independent variables on nurse performance is 81.7%, while the remaining 18.3% is influenced by other factors not examined in this study. Thus, if the leadership style, work culture, and workload increase, the performance of executive nurses in the Inpatient Room of Budiasih Serang Hospital will also increase.